2008
DOI: 10.1002/mnfr.200700311
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of major proteins and fat fractions associated with mare's milk fat globules

Abstract: Although several studies have aimed to identify mare's milk proteins, only the major whey proteins and some caseins have yet been characterized. Incomplete sequencing of the equine genome and the difficulty of recovering highly hydrophobic proteins mean that little is known to date about the proteins associated with milk fat globules, which have been shown to play an important role in newborns' defense mechanisms. The fat fraction, in particular the distribution of unsaturated fatty acids, has been more extens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 43 publications
3
17
1
Order By: Relevance
“…1). The two-dimensional electrophoresis map showed a pattern very similar to that previously published for horse MFGM proteins, where lactadherin was the major protein and was identified in several spots at different molecular masses (34). The spots 1-4, corresponding to the molecular masses of horse lactadherin, were excised, and the proteins were identified by MALDI-TOF MS and PMF as the horse milk fat globule-EGF factor 8 splice variant, also known as horse lactadherin (Table 1).…”
Section: Proteomic Analysis and Protein Sequencing Indicate The Presesupporting
confidence: 79%
See 1 more Smart Citation
“…1). The two-dimensional electrophoresis map showed a pattern very similar to that previously published for horse MFGM proteins, where lactadherin was the major protein and was identified in several spots at different molecular masses (34). The spots 1-4, corresponding to the molecular masses of horse lactadherin, were excised, and the proteins were identified by MALDI-TOF MS and PMF as the horse milk fat globule-EGF factor 8 splice variant, also known as horse lactadherin (Table 1).…”
Section: Proteomic Analysis and Protein Sequencing Indicate The Presesupporting
confidence: 79%
“…When separated by two-dimensional electrophoresis, each of these proteins shows an apparent molecular mass above the theoretical value, with the difference due to glycosylation (29 -31). MFGM-associated proteins from water buffalo, sheep, and horse also have been analyzed (32)(33)(34). Comparative species-to-species structural studies among MFGM proteins showed high variation, especially for lactadherin (35).…”
mentioning
confidence: 99%
“…As a matter of fact, on day 1 fat globules are slightly over 3 µm but thereafter they show a lower dimension, between 2 and 3 µm, as reported also by Malacarne et al [9]. HM fat globules have an average diameter of 4µm [1] while for CM it is of 3-5 µm. Dimension of fat globules are very important for lipid digestion by human pancreatic lipase (hPL) as discovered by Berton et al [13].…”
Section: Fat Globule Dimensionssupporting
confidence: 74%
“…However, while the major protein components of milk have been the subject of intense research and characterization, less abundant milk proteins and peptides have lagged behind, and studies have been mostly performed in humans and bovines. In recent years, however, the study of the milk fat globule membrane protein component is receiving growing interest (Aoki, 2006;Barello et al, 2008;Bianchi et al, 2009;Cebo, Caillat, Bouvier, & Martin, 2010;Charlwood et al, 2002;Mather, 2000;Reinhardt & Lippolis, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Major MFG proteins (MFGPs) from human and bovine milk have been extensively characterized and reviewed (Mather, 2000) and several proteomic studies on MFGPs have been recently published for bovine, equine, and buffalo milk (Barello et al, 2008;D'Ambrosio et al, 2008;Reinhardt & Lippolis, 2006), while the MFGPs of small ruminants have been subjected to significantly less intense research efforts. Moreover, the two-dimensional polyacrylamide gel electrophoresis (2-DE) reference maps of sheep and goat MFGPs are not currently available.…”
Section: Introductionmentioning
confidence: 99%